2012
DOI: 10.5005/jp-journals-10024-1133
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Dental Anxiety and its Correlation with Denture Satisfaction in Edentulous Patients

Abstract: Objective The objectives of this study were to measure the level of dental anxiety and its correlation with dental history, denture satisfaction and other variables. Materials and methods A cross-sectional study was conducted on 150 completely edentulous patients reporting to the Department of Prosthodontics, KLES's Institute of Dental Sciences, Belgaum, over a period of 17 months (August 2005 to March 2007). The anxiety level of the patients was assessed with the help of a questionnaire, after obtaining an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…It is usually taken for granted that women are more demanding about esthetics than men, and so women are usually less satisfied with their dentures. Although one can argue that such cultural thinking is more suitable to old-fashioned macho mentality, some modern articles [59][60][61] have observed significant differences between genders regarding patient satisfaction with dentures.…”
Section: Gendermentioning
confidence: 99%
See 1 more Smart Citation
“…It is usually taken for granted that women are more demanding about esthetics than men, and so women are usually less satisfied with their dentures. Although one can argue that such cultural thinking is more suitable to old-fashioned macho mentality, some modern articles [59][60][61] have observed significant differences between genders regarding patient satisfaction with dentures.…”
Section: Gendermentioning
confidence: 99%
“…Other psychological issues, as depression [67], general anxiety [61], and emotional aspects related to tooth loss [68], negatively correlate with patients' satisfaction with their dentures. Given these results, it is not surprising that a recent study [69] showed that psychoeducation provided by specialists significantly improved patient satisfaction.…”
Section: Personality and Psychological Factorsmentioning
confidence: 99%
“…In many cases, the dentist may have difficulty persuading the patient to wear dentures that are well‐fitted due to psychological factors (Pasad et al, 2021 ). Anxiety is a factor that greatly affects CD satisfaction of edentulous patients (Shrivastava et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…3 , 7 Dentists should know the treatment modality for each patient situation 32 and should put in mind that the patient’s satisfaction could be jeopardies if he could not perform the correct treatment modality. 33 Therefore, assessing the factors that may influence patient satisfaction can provide a clue regarding the best dental treatment.…”
Section: Introductionmentioning
confidence: 99%